Damage control and intramedullary nailing for long bone fractures in polytrauma patients. (June 2017) - Patka, Peter
Abstract: The early fracture treatment in patients with multiple injuries should be focused on damage control. The fracture type and its location, local soft tissue condition as well as the patient's physiological condition shall determine the time and type of fracture treatment. Prevention of local and systemic complications must be immediately considered and included in the treatment planning. The use of external fixator (ExFix), which will be replaced by IM-implants in most cases at a later stage, provides adequate temporary fracture stabilization with less collateral damage. Good clinical results can be expected in patients with long bone fractures if the principles of damage control surgery are applied and local complications are prevented through proper reduction, firm fixation, early soft tissue reconstruction, and early rehabilitation.